Trends Analysis Between The Relationship Rice Harvest and Rice Productivity in Nusa Tenggara Province - Hamdiah, Yulinda Raudatul; Robbaniyyah, Nuzla Af'idatur (Program Studi Matematika, 2025)
This study aims to analyze the monthly trends in rice productivity and harvested area in West Nusa Tenggara (NTB) Province in 2023 and identify the relationship between these two variables. The data used in this research were obtained through a rice crop cutting survey based on the Area Sample Frame (KSA) method conducted by the Central Statistics Agency. Productivity was calculated based on the amount of yield produced per unit area of land each month. The results showed that rice productivity in NTB Province fluctuated, with the highest productivity recorded in January at 56.54 quintals per hectare (ku/ha) and the lowest in June at 48.40 ku/ha. Similarly, the harvested area varied, with the largest area recorded in March at 73,766 hectares and the smallest in December at 5,382 hectares. The analysis of the relationship between harvested area and rice productivity revealed an inverse pattern, where an increase in harvested area was not always accompanied by an increase in productivity. Therefore, rice productivity and harvested area are more influenced by external factors and do not directly affect each other.